Rancang Bangun System Otomatisasi Pencegahan Overload Deck Conveyor pada Kapal CCL Padmasari - Bangkit Risang Nugroho; Edi Kurniawan; Rika Fitriani (Pusat Riset dan Inovasi Nasional, 2025)
Coal as an alternative energy is widely found in Indonesia. To support the coal distribution process, a means is needed in the form of a floating conveyor ship that will distribute coal from the barge to the bulk carrier in very large quantities. This research aims to examine the system that occurs on the ship from the original speed changed manually using a potentiometer to automatically using the fuzzy logic method. The process of this tool works by changing the speed automatically using the fuzzy method, entering the input membership into the fuzzy membership then the parameters are detected by the sensor, the results of the detection are displayed on the LCD layer. The methodology and design of this system will be carried out using the experimental method where this method creates a new product with several trials so that later this tool can increase efficiency during the loading and unloading process on the ship, and it is tested to what extent the sensor can detect the load quickly using the fuzzy method. The results of this overload prevention system show that the system can work optimally in reading the load, as well as the accuracy of the sensor which can read the amount of load very quickly in less than 1 second.